2018
DOI: 10.1139/cjas-2017-0092
|View full text |Cite
|
Sign up to set email alerts
|

In situ ruminal digestibility of red osier dogwood in finishing beef heifers

Abstract: An in situ study was conducted to determine the effect of feeding red osier dogwood (ROD) on ruminal digestion of barley, ROD, and barley silage in beef heifers. Heifers were fed diets that varied by substituting ROD for barley silage at 0%, 3%, 7%, or 10%. Slowly degradable fraction and effective degradability (ED) of ROD crude protein (CP) linearly (P < 0.02) increased with increasing ROD. The ED of CP of barley and barley silage was reduced (P < 0.01) by feeding ROD. These results indicate that feedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…As digestion of CF and microflora responsible for its digestion are stimulated under rumen condition with high pH. Several studies demonstrated that plants with antioxidant and anti‐inflammatory activities as SM showed mixed or varied effects depended on the dose used (Gomaa, Wei, et al, 2018; Wei et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…As digestion of CF and microflora responsible for its digestion are stimulated under rumen condition with high pH. Several studies demonstrated that plants with antioxidant and anti‐inflammatory activities as SM showed mixed or varied effects depended on the dose used (Gomaa, Wei, et al, 2018; Wei et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Another study indicated that increasing dietary cornus was beneficial for the NDF digestibility and also decreased protein degradability, providing a higher concentration of bypass protein. Moreover, in the same study, cornus contributed to the mitigation of acidosis, affecting cattle fed high-grain diets, by altering the nutrient degradability of feeds [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another plant commonly found in the Mediterranean area is Cornus spp., with a high antioxidant activity due to its large total phenolic concentration of about 220 mg/dL gallic acid equivalents [ 18 ]. The most important phenolic compounds of cornus are anthocyanins, gallic acid and ellagic acid, which all have antioxidant and antimicrobial activity [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, differences in the CP content between the basal and DDGS diets (basal vs. DDGS; 13.9 vs. 19.6% CP) were expected to result in differences in NH 3 -N concentration, microbial protein synthesis, or CP degradability. Gomaa et al (48) reported that the in situ rumen degradation rate linearly decreased for silage protein, but it was not changed for grain protein when heifers were fed diets containing ROD. Wei et al (5) suggested that phenols in ROD have a greater protein-binding capacity with soluble protein than with insoluble protein.…”
Section: Interaction Of Ddgs Inclusion and Rod Extractmentioning
confidence: 99%